Effect of Nepeta glomerulosa Boiss. Aerial Parts Aqueous Extract on Morphine Withdrawal Syndrome in Mice: Effect of Nepeta glomerulosa extract on morphine withdrawal syndrome - Hosseinzadeh, Hossein; Ziaee, Toktam (Iranian Journal of Pharmaceutical Sciences, 2006)
The effect of aqueous extract of Nepata glomerulosa Boiss. aerial parts on morphine withdrawal syndrome was investigated in mice. Dependence was induced by subcutaneous injections of morphine for 3 consecutive days. On day 4, morphine was injected 2 h prior to intraperitoneal injection of naloxone. The number of jumps during a 20 min. period after naloxone injection was considered as a measure of the withdrawal syndrome. Open field and rotarod tests were also performed. The results indicated that the aqueous extract (0.1 to 2.8 g/kg, s.c.) and diazepam (5 mg/kg) reduced the number of jumps (58±2.3 to 10±0.82, p<0.001 vs normal saline, 87±3.4). The extracts also reduced motion balance and locomotion activity. It is concluded that the aqueous extract of N. glomerulosa aerial parts could diminish morphine withdrawal syndrome.